Instructional Leadership of School Administrators in Prachinburi Primary Educational Service Area Office 1 - Klinhom, Rungsalid; Thongprong , Amnuay (Journal of Liberal Arts RMUTT, 2024)
The objectives of this research were: 1) to investigate the instructional leadership of school administrators according to the opinions of teachers affiliated under the Prachinburi Primary Education Area Office 1; 2) to compare the instructional leadership of school administrators according to the opinions of teachers affiliated under the Prachinburi Primary Education Area Office 1, categorized by educational qualification, academic status, work experience, and school size. The research samples consisted of 301 teachers in schools affiliated under the Prachinburi Primary Education Area Office 1, using a predefined table size from Cohen et al. for sample size calculation. The research instrument used was a questionnaire with a 5-point Likert scale presenting Cronbach’s alpha reliability coefficient of 0.989. The statistical analysis methods consisted of percentage, frequency, mean standard deviation, t-test, one-way ANOVA, and pairwise comparisons of means using Scheffe’s method. The research results showed that the overall mean score and each area were at a high level, with the mean score ranking from highest to lowest, including mission planning, student progress assessment and monitoring, academic atmosphere promotion, curriculum, and learning management, respectively. For the overall aspect and each area, there were no statistically significant differences in teachers’ qualifications and teachers’ academic status, except curriculum management and learning management, which showed a statistically significant level of .05. The teachers’ teaching practices in schools of different sizes did not show the overall differences. Considering each area, it was found that in mission planning, there were statistically significant differences at the .05 level between small and medium-sized schools and between small and large schools, as well as in curriculum management and learning management between small and large schools and between medium-sized and large schools, with statistically significant differences at the .05 level.